The Oral Microbiota: A Literature Review for Updating Professionals in Dentistry. Part I - Barboza-Solís, Cristina (2019)
In recent decades, a body of literature examining the relationships between oral health and general health has rapidly developed. However, the biological mechanisms involved in explaining such relationships have not been fully described. Recent evidence has suggested that these relationships could be partially explained by the composition and interaction of the microbiome/microbiota between local and systemic body sites. For instance, it has been suggested that intestinal microbiota could have effects on non-communicable diseases, such as diabetes or cardiovascular diseases. The objective of this study is to explore current evidence of the link between oral and systemic diseases, to discuss whether oral microbiome/microbiota could represent an unexplored biological pathway partially explaining those relationships. A non-systematic review of the literature was carried out using keyword searches in Pubmed from February to May 2019. The ultimate goal was to present recent scientific evidence to update the general knowledge on this topic to professionals in dentistry. This review is divided in two parts for journal publication; however, it is intended to be used as one piece. In this first part, we will summarize the conceptual background of oral microbiome/microbiota, we will describe the main methods used in microbiology to characterize oral organisms, and will present the main composition of bacteria in oral microbiome/microbiota. The second part highlights the main evidence regarding the biological plausibility that links oral microbiome and systemic diseases and we will conclude with some future research recommendations. Taking into account the role of oral microbiota in the development of systemic diseases could change the main paradigm of how oral health is currently conceptualized by dental professionals.